Prostituzione e sfruttamento tra vulnerabilità, familismo e segregazione sociale: il caso delle donne Rom - Baldoni, Emiliana (SocietàMutamentoPolitica, 2021)
The article faces the issue of the sexual exploitation of Roma women, assuming that their marginal position in the global prostitution market, as a system that reflects the social inequalities, is the product of the inextricable intertwining of individual vulnerability factors and the condition of segregation. In Italy, the situation of extreme marginality that characterizes the so-called “nomad camps”, on an equal terms with other non-Roma women, increases the risk of violent exploitation and reduces the possibility of emancipation and self-determination. Therefore, even if they represent a minority of the total number of exploited women, the protection of Roma women requires the implementation of ad hoc measures within a global approach aimed at overcoming the “nomad camps”.